PENERAPAN STRATEGI THE FIRING LINE UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (PAI) PADA MATERI SIFAT JAIZ BAGI ALLAH SWT SISWA KELAS IV SDN 005 KOTO PERAMBAHAN KECAMATAN KAMPA KABUPATEN KAMPAR - Zulparis Zulparis (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is a classroom action research. The formulation of the problem in this research is whether theapplication of the firing line strategy can improve the learning outcomes of Islamic religious education materialnatural of jaiz for Allah SWT grade IV students SDN 005 Koto Perambahan Kecamatan Kampa KabupatenKampar? This research aims to increase learning outcomes Islamic religious education grade IV SDN 005 KotoPerambahan Kecamatan Kampa Kabupaten Kampar through the strategy of the firing line. The research wasconducted two cycles. The data outlined are prior to action, in cycle I and cycle II. Each cycle is done in twomeetings. As for the stages in each cycle, that is 1) action planning/ preparation, 2) action implementation, 3)observation, and 4) reflection. Based on the research result of the application of the firing line strategy on PAIsubjects, it is known that there is an increase in learning outcome test from before action, cycle I to cycle II.Before the students learning outcomes were medium by percentage with an average of 56.8%, there is anincrease in learning outcomes from cycle I to cycle II. In the cycle I, students learning outcomes were 72.2% inthe medium category. In the cycle II, students learning outcomes were 85,2% in the good category. From theabove data it is known that the results of student learning on the subjects of Islamic religious education on thematerial nature of jaiz for Allah SWT can be increased through the application of the strategy of the firing line.